Domestikasi Bidens pilosa L. sebagai Tanaman Herba Antivirus Potensial dengan Komposisi Media dan Cekaman Kekeringan - dhea alief rahmasari; Siti Asmaniyah Mardiyani; Maria Ulfah (AGRONISMA, 2021)
Bidens pilosa L. (ketul) belongs to the wild-growing Asteraceae family. The young leaves of this plant are usually used as a mixture of fresh vegetables or useful in treating several diseases. In the absence of research on the recommended planting media and the many benefits of Bidens pilosa L., this underlies the efforts to develop this plant. This study aims to determine the interaction of media composition and watering intervals on a drought stress scale on the growth, yield and quality of Bidens pilosa L. The study was conducted at the Plastic House in February-April 2021, located at Jalan Cempaka Sari No. 20 Dusun Buwek Rt 04 Rw 04 Sitirejo Wagir Village on a piece of land in the middle of a village with an area of 5.8Ã—3.9 meters Plastic House. And the analysis was carried out at the Laboratory of the Faculty of Agriculture, Islamic University of Malang. This study used a factorial randomized block design (RAK) experimental method. Factor 1 media composition (K) which consists of 3 levels, namely K1 = Soil + Manure (1:1); K2 = Soil + Manure + Husk Charcoal (1:1:1) and K3 = Soil + Manure + Husk Charcoal (2:1:1). Factor 2 water stress (C) which consists of 3 levels, namely C1 = Water Sprinkling Interval once a day; C2 = Watering Interval every 3 days and C3 = Watering Interval every 6 days. Each treatment was repeated 2 times with 3 samples. The results of this study showed that in general the composition of the media and the watering interval (drought stress) had a significant effect on plant growth, yield and quality, namely on the variables of leaf area, stem diameter, total plant fresh weight, economic weight and chlorophyll analysis. In general, the best treatment is K1 = Soil + Manure (1:1); K2 = Soil + Manure + Husk Charcoal (1:1:1) and C3 = Water Watering Interval every 6 days. This shows that by giving the media composition K3 = Soil + Manure + Husk Charcoal (2:1:1) does not give better results than K1 = Soil + Manure (1:1) and K2 = Soil + Manure + Charcoal Chaff (1:1:1).